Matachines in the Midwest: Religion and Identity in the American Heartland - Christ, Stephen R. (Qualitative Sociology Review, 2016)
This article examines how a community of recent Mexican migrants and their families use popular religious practices to sustain a sense of ethnic Mexican identity in a predominantly White rural Catholic Church where their growing presence and influence are changing how Catholicism is practiced. In this rural setting, participation in a Matachines dance tradition functions to bring the Mexican community together, place before them a common tradition uniquely their own, and build up distinctive emotions in them around ritual traditions which in turn serve as a pillar of strength for maintaining their ethnic identity through the perpetuation of religious practices and symbols. More specifically, two dimensions are of central focus in this article: tensions arising from ethnic expressions through the institutional Church and the contested meanings of specific rituals and religious symbols such as Matachines and La Virgen de Guadalupe. Based on two years of ethnographic fieldwork, this research presents evidence of a modern transformation of U.S. religious practices as a result of immigration from Mexico into the Midwestern United States.